Oral Prolonged‐Release Oxycodone‐Naloxone: Analgesic Response, Safety Profile, and Factors Influencing the Response in Patients With Advanced Cancer. Issue 6 (22nd April 2019) - Corli, Oscar; Iorno, Vittorio; Legramandi, Lorenzo; Rulli, Eliana; Roberto, Anna; Azzarello, Giuseppe; Schiavon, Stefania; Cavanna, Luigi; De Santis, Stefano; Cartoni, Claudio; Di Marco, Pierangelo; Dauri, Mario; et al.
Abstract: Background: Oxycodone‐naloxone (OXN) aims to reduce opioid‐related constipation while being successfully analgesic. Methods: We evaluated the analgesic response, prevalence, and severity of side effects in 176 patients with cancer who had moderate to severe pain and were being treated with OXN. Patients were followed for 28 days and evaluated every 7 days. Pain intensity, changes of therapy, and adverse drug reactions were recorded at each visit. The primary efficacy endpoint was the proportion of responders (≥30% reduction of pain intensity from baseline to final) and final average pain score ≤ 4 on a scale of 0 to 10. Results: Average and worst pain intensity and breakthrough pain (BTP) prevalence decreased over time, and 81.3% of patients were responders. The starting daily dose of OXN was raised from 25.1 ± 13.0 mg to 44.1 ± 29.9 mg, and dose escalation > 5%/day was observed in 19.4% of patients; 40.8% to 46.2% and 11.0% to 17.0% experienced any constipation and a severe grade of constipation during the follow‐up visit, respectively. Digestive system tumor, thyroid endocrinopathies, psychological irritability, and BTP increased the risk for analgesic nonresponse. Conclusions: OXN had a strong analgesic effect in patients with moderate to severe cancer pain; the safety profile is in line with the common adverse effects of opioids, and severe constipation was uncommon. Clinical Trial Registration: NCT02293785.